Islam Nusantara: A Middle Way? - Luqman Nurhisam (SHAHIH: Journal of Islamicate Multidisciplinary, 2016)
Islam Nusantara is not a new thing. The word “Islam” combined with “Nusantara” is not only confirmed the name, but also the characters to show the pattern of a heterogeneous entity. The concept of Islam Nusantara face (vis a vis) with Islam in the Middle East (Islam Arab). Diversity as a typology of Islam Nusantara is the result of the struggle that the length between religion and dimensions of life (social, economic, politic, culture and etc.), the text of the context that complement one another so that spawn Islam friendly, peaceful, anti-radical, harmony and rahmatan lil 'alamin. Departing from the historical and epistemological approach, this article tries to provide a long discourse that was raised again in the “Declaration of Nahdlatul Ulama” at the International Conference of Islamic Leaders Moderate (ISOMIL) which took place from 9 to 11 May in Jakarta. The purpose of writing this article is actually also want to answer the issues pointed out that Islam Nusantara models reflect the teachings of Islam are not singular. Islam Nusantara bukanlah hal yang baru. Kata “Islam” digabungkan dengan “Nusantara” tidak hanya soal nama, tetapi juga karakter yang menunjukkan pola keberagaman.  Konsep Islam Nusantara dihadapkan dengan Islam Arab.  Keberagaman sebagai tipologi Islam Nusantara adalah hasil dar perjuangan yang panjang antara agama dan dimensi kehidupan (sosial, ekonomi, politik, budaya dan lain-lain), teks konteks yang melengkapi satu dengan lainnya yang menjadikan Islam ramah, damai, anti-radikal, harmonis dan rahmatan lil’alamin.  Berangkat dari pendekatan sejarah dan epistemologis, artikel ini berusaha untuk memberikan wacana lama yang dimunculkan kembali pada “Deklarasi Nahdlatul Ulama” pada Konferensi Internasional Pemimpin Islam Moderat (ISOMIL) yang berlangsung pada 9 sampai 11 Mei di Jakarta.  Tujuan dari penulisan artikel ini sebenarnya juga untuk menjawab isu yang menyebutkan bahwa Model Islam Nusantara mencerminkan ajaran Islam yang tidak tunggal.